Patroc??nio esportivo nos jogos Rio 2016: estudo de caso de um fornecedor de materiais - Valle, Thalles Sanches (2016)
Qualitative research that had the objective to analyze the sole supplier sponsorship of the Weightlifting during the Rio 2016 Olympic Games, seeking to comprehend which are the expected benefits and the results of that investment. To reach this goal the following literature background were raised: sport sponsorship, which can be comprehended as when an enterprise allocate resources directly or indirectly into an athlete, competition, teams or sports organizations; co-branding which???s when both brands explore their similar elements, or together build a new concept; as well as other things such as doping cases and their influences into the area. Then it was necessary to prospect the context of the sponsorship during the Olympic Games and it???s financial aspects over the time, realizing according to the literature background that some cases tends to have more return than some others and that???s where the planning of this qualitative research which involves ZKC (Zhangkong Barbell Company) reach the needs to interview the proprietor of the enterprise, the Brazilian team leader for weightlifting during Rio 2016 and five spectators in the place where the competition were held, to comprehend their view over this sponsorship. The collected data were treated by content analysis and categorized as their occurrence. After categorizing and analyzing the data is when this research presents the spontaneous return with specialized media, which in this case was a website and in more than 100 notes published only 1, mentioned the sponsor. The proprietor of the enterprise related that they aimed to promote the brand in this event and to do it, they made a partnership with the International Weightlifting Federation (IWF), that contemplated others actions such as supplies donations, which in fact happened. The five interviewed spectators (100%) did not recognized the brand as sponsor, and three of them (60%) also mentioned another brand, but also, three spectators after knowing that ZKC was the sponsor, related the brand to quality of the event. The results demonstrated that to exist a spontaneous return from this action of sponsorship the supplier has to communicate this partnership to the public, through social media or somewhere else, or even buying some other properties of the event (such as the logo of the brand on the competition material), that turns possible to the brand to appear. Other actions such as equipment donations and also promoting events are recommended.